GROWING PUBLIC DEBT AS A RESULT OF THE COVID-19 PANDEMIC IN THE WESTERN BALKANS REGION: THE CASE OF NORTH MACEDONIA AND SERBIA - Kisin, Jovana (Poslovna ekonomija, 2022)
Just before the start of the pandemic, the public debt of the Western Balkan countries averaged over 50% of GDP, with large fluctuations between countries, which narrowed the fiscal space for resolving the consequences of the COVID-19 crisis. Despite that, although partially stable to pandemic turbulence, the needs for borrowing in the countries of the Western Balkans are growing sharply, as a result of which future interest payments are increasing in the conditions of increased public debt. It is estimated that all countries in the region will record an increase in public debt, while Montenegro will have the highest level of growth. That is why the countries of the Western Balkans need to implement successful fiscal consolidation and more prudent fiscal management at the national level, but also to pay attention to higher government borrowing and increased public investment in pandemic conditions. The aim of this paper is to analyze the movement of public debt of the countries in the region in the crisis caused by the COVID-19 pandemic, with special emphasis on the case of North Macedonia and the Republic of Serbia. The paper consists of three parts. After the introduction, the first part of the paper presents an analysis of public debt in the Western Balkans region. The second part analyzes the public debt in the case of the Republic of Serbia, while the third part deals with the analysis of the public debt in the case of North Macedonia. Finally, concluding remarks are given.